Penyalahgunaan Wewenang Dalam Pengangkatan Pejabat Pimpinan Tinggi - Hatta, Dodi Fahtur Mutttaqim; Salmon, Hendrik; Alfons, Saartje Sarah (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: The appointment of a high-level official, namely the Regional Secretary by the Governor according to his authority as stipulated in laws and regulations, is a form of implementation of the principle of legality in the rule of law principle.Purposes of the Research: This study aims to find out whether the governor has the authority to appoint acting regional secretary, and whether the actions of the governor of Maluku to appoint acting regional secretary of Maluku are legal actions.Methods of the Research: This study uses the normative legal research method, which aims to find out whether the governor has the authority to appoint acting regional secretary, and whether the actions of the Maluku governor who appointed the acting regional secretary of Maluku are legal actions.Results / Findings / Novelty of the Research: The Governor as the representative of the Central Government in the regions has the authority to appoint Acting Regional Secretary with the approval of the Minister of Home Affairs if the Regional Secretary is unable to carry out his duties and there is a vacancy in the position of Regional Secretary. Therefore, the Governor cannot appoint an Acting Regional Secretary if there is no vacancy in the position of Regional Secretary. The appointment of the Acting Regional Secretary by the Governor of Maluku did not meet the procedural and substance requirements because Kasrul Selang as Regional Secretary could not be dismissed from his position before 3 February 2022. This means that the dismissal of Kasrul Selang on 10 December 2021 clearly resulted in the appointment of the acting regional secretary not meeting the requirements.